PELATIHAN PELVIC ROCKING UTNTUK MENGURANGI NYERI PUNGGUNG PADA IBU TRIMESTER III DI BPM ISLAH WAHYUNI - Yessi Azwar; Linda Suryani; Eva Santi Hutasoit; Siska Mulyani; T. Hartian Silawati Ningsih; Noviyanti Noviyanti; Rusherina Rusherina; Novi Yanti; Ulfa Hasana (LPPM Universitas Abdurrab, 2022)
Lower back pain is a common complaint felt by pregnant women, especially when entering pregnancy in the third trimester. The pain felt by the mother also varies. There are various nonpharmacological therapies that can be done to help mothers relieve back pain during pregnancy, one of which is pelvic rocking. Pelvic Rocking training is given to third trimester mothers to reduce back and back pain in mothers. This training is given continuously to the mother until the mother is proficient in carrying out pelvic rocking in daily activities. This training is given to mothers who are in BPM Islah Wahyuni. The purpose of this training is to educate pregnant women in the THIRD Trimester on how to reduce pain with Pelvic Rocking. The target of this community service activity is pregnant women in the third trimester at BPM Islah Wahyuni. This activity was held for 3 months, namely January - March 2022 with one meeting every month. The activity was held from 09.00 - 11.00 WIB. The average intensity of back pain before being given Pelvic Rocking is with a minimum value of 3 and a maximum value of 4, while the average intensity of back pain trimester III after being given Pelvic Rocking is with a minimum value of 0 and a maximum of 2.